Bitter Taste Perception and Dental Biofilm Cariogenicity in Orthodontics - Nithivoot Luengthamchat; Sittichai Koontongkaew; Kusumawadee Utispan (Elsevier, 2022)
Background: Bitter taste perception and sweetness preference have been associated with dental caries. Propylthiouracil (PROP) has been used to determine the genetic sensitivity to bitter taste in early childhood caries. However, the role of the bitter threshold in dental biofilm cariogenicity has not been reported. The purpose of this study was to investigate the role of individual taste sensitivity using PROP in dental biofilm cariogenicity in orthodontic patients. Methods: Forty orthodontic patients (12-42 years old) undergoing fixed appliance orthodontic treatment participated in this cross-sectional study. Their demographic, oral hygiene practice, and dietary habits data were obtained using a questionnaire. The patients' bitter taste threshold was measured using a PROP assay. The patients were subsequently classified as super-tasters (STs), medium-tasters (MTs), and non-tasters (NTs). Dental biofilm cariogenicity was determined using a 3-tone disclosing gel that becomes pink (new dental biofilm), purple (mature dental biofilm), and light blue (cariogenic dental biofilm) based on dental biofilm maturity. Results: The NT, MT, and ST groups comprised 10%, 27.5%, and 62.5% of the patients, respectively. Most of the STs (56%) and MTs (63.6%) were female, whereas no females were NTs. The dental biofilm cariogenicity was significantly different between the PROP bitterness groups (P < .05). The highest percentage of mature biofilm, followed by cariogenic and new biofilm, was found in the MT and ST groups. However, the cariogenic biofilm percentage was significantly higher compared with mature biofilm (P < .05) in the NT group. A low frequency (<1 time/d) of sugary and acidic food intake between meals was observed in the ST, MT, and NT groups with no significant difference amongst the groups (P > .05). Conclusions: Cariogenic dental biofilm was highly present in orthodontic patients with the NT phenotype.